2022
DOI: 10.1177/02676591221075934
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of ventilation/perfusion single photon emission computed tomography/computed tomography and multidetector computed tomography angiography for the detection of acute pulmonary embolism in clinical practice

Abstract: Introduction Computed tomography angiography (CTA) and ventilation/perfusion (V/Q) single photon emission computed tomography/CT (SPECT/CT) images have been widely used to detect PE, but few studies have performed a direct comparison between them. We aimed to evaluate the performance of these tests in the same group of patients, selected from the routine practice of a general hospital. Methods Patients with suspected acute PE were prospectively submitted to CTA and V/Q SPECT/CT. General radiologists and nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…The number of enrolled patients ranged from 28 44 to 314 41 patients, for a total of 1,086 patients. One study 45 included all patients with cancer, while Bhatia and colleagues 46 included patients with or without pre-existing lung disease.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of enrolled patients ranged from 28 44 to 314 41 patients, for a total of 1,086 patients. One study 45 included all patients with cancer, while Bhatia and colleagues 46 included patients with or without pre-existing lung disease.…”
Section: Resultsmentioning
confidence: 99%
“…SPECT acquisitions were conducted using the following parameters: energy window was 140 KeV for 99m Tc in 5 studies 43 45 46 47 48 (no data were reported in the other 3 studies 41 42 44 ); time for projection ranges from 10 to 25 seconds; number of projection ranges from 30 to 128 for an orbit of 180° to 360° in 6 studies 42 43 44 46 47 48 (no data were reported in the other 2 studies 41 45 ); matrix was 128 * 128 in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations